Faktor Yang Berhubungan Dengan Kejadian Infeksi Saluran Pernafasan Atas Pada Balita - Nur Syamsi (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
The purpose of this study was to determine factors related to the incidence of upper respiratory tract infections in infants. The research method, this research is a descriptive study using cross sectional study design. A cross sectional study is a study in which variables included in risk factors and variables included in effects are observed at the same time. The results of the study, there is a relationship between nutritional status, smoking habits, density of occupants, maternal education and immunization status on the incidence of upper respiratory tract infections in infants. Conclusion, the dissemination of information about upper respiratory infections so that the community always does not allow their children to be exposed to risk factors for upper respiratory infections, awareness of parents, especially those who like to smoke so as not to smoke in the home environment because it will affect the health of the respiratory tract, especially in infants so it must be done socialization of the dangers of smoking to the community by local health workers. Immunization is one of the factors affecting the incidence of upper respiratory tract infections in infants, so there is a need for counseling about the importance of immunization in infants by local health workers.